Improvement of innovative policy in agriculture - M. K. Ashinova; A. K. Dorgushova; S. K. Yeshugova (Новые технологии, 2019)
The introduction of innovations in the agro-industrial complex is one of the effective and accelerated development opportunities that will ensure the food security of the country. To ensure economic growth in agriculture and increase its competitiveness, constant updating of technologies is necessary.The scope of application of innovative technologies in large enterprises, the smallest ones in small enterprises and farms and the performance of scientific institutions have been considered.The purpose of the article is to determine the direction of improving the scientific and technological policy in agriculture by assessing the current level of application of innovative technologies in agriculture. At the same time, modern methods of scientific knowledge have been used, such as analysis, synthesis, induction, abstraction.The article identifies factors that affect the competitiveness of domestic agricultural technologies.Based on the identified factors, the directions of improving the scientific and technological policy in agriculture have been identified: the formation of modern institutions for the innovative development of the agricultural sector, increasing budget support for agricultural science and stimulating the flow of private investment in agricultural research and development.